Study of pre-precipitated δ phase promoting deformation twinning and recrystallization behavior of Inconel 718 superalloy during hot compression. (February 2023) - Jiang, Wenxiang; Lu, Junxia; Guan, Hao; Wang, Mingming; Cheng, Xiaopeng; Liu, Linlin; Liu, Xianqiang; Wang, Jin; Zhang, Yuefei; Zhang, Ze; Lin, Weitong; Hu, Jing
Graphical abstract: Highlights: The promoting effect of pre-precipitated δ phase on deformation twinning and recrystallization behavior of Inconel 718 superalloy during hot compression was studied systematically. The promoting effect on the formation of deformation twins was attributed to the lower stacking fault energy (SFE) and the local stress concentration. A novel heteroepitaxial recrystallization (HERX) mechanism was found based on inverse precipitation. Abstract: The delta (δ) processing strategy is an efficient heat treatment to refine and homogenize the grain microstructure of Inconel 718 superalloy (IN718). However, the microstructure becomes complicated by the effect of pre-precipitated δ phases, due to the coupling of precipitations, high temperature, and loading stress. The present study aims to clarify the effect of δ phases on the microstructure evolution of IN718, especially the promoting effect on deformation twins (DTs) and dynamic recrystallization (DRX) behavior. The results show that the promoting effect of δ phases on the formation of DTs was attributed to the lower stacking fault energy (SFE) caused by the precipitation of δ phases and the local stress concentration caused by the distribution of δ phases. The area fraction of DRX grains in the compressed δ-containing specimen was 21% higher than that in the compressed δ-free specimen, which was associated with the discontinuous dynamic recrystallization (DDRX) nucleation stimulated by the single δ phase and the continuous dynamic recrystallization (CDRX) nucleation promoted by the distribution of δ phases. Furthermore, a novel heteroepitaxial recrystallization (HERX) mechanism was found based on inverse precipitation from the undissolved δ phase to γ matrix phase grains with a crystallographic orientation relationship of (0_10)[1 0 2]δ //(__111)[0 1 1]HERX .